1982
DOI: 10.1007/bf01656386
|View full text |Cite
|
Sign up to set email alerts
|

Lymphography of the breast as an accessory in the early diagnosis and detection of carcinoma of the breast: Lymphography as a prognostic tool

Abstract: Radionuclide lymphography of the internal mammary and axillary lymph nodes performed on 63 patients with suspected carcinoma of the breast showed good correlation with the histological findings. Twenty‐seven of these patients proved to have carcinoma, 14 with lymph node involvement and 13 without. The remaining 36 had benign lesions. Radionuclide lymphography was accurate in 60 of the 63 cases (95%), giving a sensitivity of 13/14(93%) and a specificity of 47/49(96%). Thus, the technique appears to be sufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Large randomized trials have proved that breast conservation treatment saves the breast and results in long-term survival rates equivalent to those after modified radical mastectomy. [1][2][3][4][5][6][7] Because clinicians have been unable to identify axillary metastases accurately using noninvasive methods, [8][9][10][11][12][13][14] axillary lymph node dissection (ALND) has continued to be an integral part of breast cancer staging and regional control. 15 However, numerous trials have demonstrated no improvement in overall survival after ALND vs observation for patients with clinically negative nodes.…”
mentioning
confidence: 99%
“…Large randomized trials have proved that breast conservation treatment saves the breast and results in long-term survival rates equivalent to those after modified radical mastectomy. [1][2][3][4][5][6][7] Because clinicians have been unable to identify axillary metastases accurately using noninvasive methods, [8][9][10][11][12][13][14] axillary lymph node dissection (ALND) has continued to be an integral part of breast cancer staging and regional control. 15 However, numerous trials have demonstrated no improvement in overall survival after ALND vs observation for patients with clinically negative nodes.…”
mentioning
confidence: 99%